Biophysics - Glaser, Roland (Springer, 2001)
The messageof this book is that biophysics is the science of physical principles underlaying the "phenomenon life" on all levels of organization. Rather than teaching "physics for biologists" or "physical methods applied to biology", it regards it's subject as a defined discipline with its own network of ideas and approaches. The book statrs by explaining molecular and supramolecular structures of biological systems, various kinds of atomic, molecular and ionic inter actions movements, energy transfer, slef organization of supramolecular structures and dynamic properties of biological membranes. It then goes onto introduce the biological organism as a non-equilibrium system, before treating thermodynamic concepts of osmotic and electrolyte equilibria, currents and potential profiles as well as mechanical and electrical properties of biological materials. Further treated are topics of environmental biophysics and such medical aspects as the influence of electromagnetic fields or radiation on living systems and the biophysics of hearing and noise protection. The book concludes with a discussion of system analysis, including models of neural processes as well as of ecological interactions, growth, differentation and evolution.